Parasitological, microbiological, and antimicrobial resistance profiles of raw and drinking water in a tourist city in the tri-border region of South America. (18th January 2022) - Scherer, Gustavo Strieder; Leal, Diego Averaldo Guiguet; Greinert Goulart, Juliane Araújo; Araújo, Ronalda Silva; Beux, Marcia Regina; Moreira, Neide Martins
Abstract: Despite the large amounts of freshwater available in Brazil, the deterioration of surface water can represent a risk of waterborne disease for national and international tourists. The main goal of this study was to assess the quality of drinking water in the triple border region of Brazil before and after being treated in water treatment plants (WTPs) and in Municipal Early Childhood Education Centers (MECECs), in terms of parasitological, microbiological, and physical–chemical aspects. Different water samples were monitored: raw water (RW), treated water (TW), and tap water from the MECECs, giving 60 samples in total, to investigate the presence of Giardia and Cryptosporidium, microbiological indicators, Pseudomonas aeruginosa, and antimicrobial resistance profiles using conventional microbiological assays and parasitological, immunological, and molecular techniques. The results obtained were compared with the reference values recommended by the legislation of drinking water in Brazil. For the first time, contamination by Cryptosporidium and Giardia was demonstrated in RW used to supply WTPs, in TW of Foz do Iguaçu, and in water destined for consumption by children. A total of 52 bacterial isolates were obtained, with high percentages of multidrug resistance to antibiotics, including a carbapenem-resistant profile, highlighting the need to improve quality control standards. HIGHLIGHTS: Waterborne pathogens were monitored in different water treatment plant phases. Cryptosporidium and Giardia were detected in raw and treated water. Contamination by pathogens and fecal bacteria was found in the distribution system. There was a heterogeneity of antimicrobial resistance patterns among bacterial isolates. A carbapenem-resistant profile was identified for Pseudomonas aeruginosa and Escherichia coli . Graphical Abstract